Regulation rather than Tenure in Policy Making; Case Study: Interaction Pattern of Public Libraries and Municipal Libraries of Tehran Municipality - Hasan Shirazi (دولت‌پژوهی, 2020)
As a concept that has spread from economics to other fields, Regulation refers to sovereign interventions aimed at the realization of the public interest. The present article focuses on the clarification of the concept of regulation in reforming the policy approach to the status of public libraries. The key question of the research is, from a policy-making perspective, in the conceptual bipolar framework of regulation and tenure, what is the relationship between the public libraries institution and the Tehran municipal libraries (which is a larger set of entities)? In this regard, the research has investigated the structural interaction of Tehran Public Libraries and Municipalities with the theoretical framework of institutionalism and qualitative content analysis method. At present, the public libraries institution is a policy maker, an administrator, and a supervisor of public libraries. In such circumstances, such affairs as obtaining a license and the duty of the municipality to pay half of its revenue to public library associations, which of course refuses to pay, has become a serious challenge between the two institutions. This study argues that even if the institution's wishes are met, a larger problem persists, and that the institution's tenure may not give a good prospect of achieving its goals. What the libraries institutions is pursuing is having hundreds of libraries with thousands of executive officer that would then be left out of their policymaking and supervisory duties. The policy-making proposal of the paper is to harmonize the integrated network of national libraries, to define the role and position of policymakers at different levels, and to distinguish the role of policymaking from implementation for public libraries. In this way, the movement of public libraries towards regulation in the role of policymaker and supervisor can serve the intended purpose. In this case, the municipality will play the role of the executor of the institution policies within the framework of the integrated urban services system.